Survival analysis of breast cancer patients in Yogyakarta. Issue 1 (January 2021) - Ivan Ariful Fathoni, M.; Gunardi; Adi-Kusumo, Fajar; Hutajulu, Susanna Hilda
Abstract: A WHO survey conducted revealed that 8-9 percent of women in the world have breast cancer. The highest cancer incidence in Indonesia is breast cancer. The highest prevalence of cancer is in Yogyakarta (4.1 / mile). This research is vital to aim to assess the length of life of patients and prognostic factors associated with survival of breast cancer patients. Research subjects were breast cancer patients who went to dr. Sardjito hospital. Subject data were taken from patient medical records from July 2018 - July 2020. This study used a survival analysis (Cox proportional hazard method), with variables used including neutrophils, lymphocytes, SGOT, albumin, chemotherapy regimens, radiotherapy, hormone therapy, karnofsky index, and stadium are independent variables that will be tested on patient survival as the dependent variable. Using kaplan meier, the -ln[-ln S(t)] curve, and the global test, it is found that all variables meet the proportional hazard assumption. Cox regression analysis used there are two stages, namely bivariate and multivariate analysis. All variables by bivariate analyzed were performed to multivariate analysis. The most significant factors based on multivariate analysis are chemotherapy regimen, hormonal therapy, and stages. This result is expected to provide medical advice regarding the proper treatment of breast cancer patients.